Murine models of sickle cell disease and beta‐thalassemia demonstrate pulmonary hypertension with distinctive features. (1st November 2021) - Buehler, Paul W.; Swindle, Delaney; Pak, David I.; Fini, Mehdi A.; Hassell, Kathryn; Nuss, Rachelle; Wilkerson, Rebecca B.; D'Alessandro, Angelo; Irwin, David C.
Abstract : Sickle cell anemia and β‐thalassemia intermedia are very different genetically determined hemoglobinopathies predisposing to pulmonary hypertension. The etiologies responsible for the associated development of pulmonary hypertension in both diseases are multi‐factorial with extensive mechanistic contributors described. Both sickle cell anemia and β‐thalassemia intermedia present with intra and extravascular hemolysis. And because sickle cell anemia and β‐thalassemia intermedia share features of extravascular hemolysis, macrophage iron excess and anemia we sought to characterize the common features of the pulmonary hypertension phenotype, cardiac mechanics, and function as well as lung and right ventricular metabolism. Within the concept of iron, we have defined a unique pulmonary vascular iron accumulation in lungs of sickle cell anemia pulmonary hypertension patients at autopsy. This observation is unlike findings in idiopathic or other forms of pulmonary arterial hypertension. In this study, we hypothesized that a common pathophysiology would characterize the pulmonary hypertension phenotype in sickle cell anemia and β‐thalassemia intermedia murine models. However, unlike sickle cell anemia, β‐thalassemia is also a disease of dyserythropoiesis, with increased iron absorption and cellular iron extrusion. This process is mediated by high erythroferrone and low hepcidin levels as well as dysregulated iron transport due transferrin saturation, so there may be differences as well. Herein we describe common and divergent features of pulmonary hypertension in aged Berk‐ss (sickle cell anemia) and Hbb th/3+ (intermediate β‐thalassemia) mice and suggest translational utility as proof‐of‐concept models to study pulmonary hypertension therapeutics specific to genetic anemias.